Improvement Research Priorities: USA Survey and Expert Consensus - Kathleen R. Stevens; John Ovretveit (Hindawi Limited, 2013)
The purpose of this study was to identify stakeholder views about national priorities for improvement science and build agreement for action in a national improvement and implementation research network in the USA. This was accomplished using three stages of identification and consensus. (1) Topics were identified through a multipronged environmental scan of the literature and initiatives. (2) Based on this scan, a survey was developed, and stakeholders (n=2,777) were invited to rate the resulting 33-topic, 9-category list, via an online survey. Data from 560 respondents (20% response) were analyzed. (3) An expert panel used survey results to further refine the research priorities through a Rand Delphi process. Priorities identified were within four categories: care coordination and transitions, high-performing clinical systems and microsystems improvement approaches, implementation of evidence-based improvements and best practices, and culture of quality and safety. The priorities identified were adopted by the improvement science research network as the research agenda to guide strategy. The process and conclusions may be of value to quality improvement research funding agencies, governments, and research units seeking to concentrate their resources on improvement topics where research is capable of yielding timely and actionable answers as well as contributing to the knowledge base for improvement.